Fear of COVID-19 Among College Students: A Systematic Review and Meta-Analysis - Fang Wang; Le Zhang; Lu Ding; Lei Wang; Yang Deng (Frontiers Media S.A., 2022)
BackgroundMental health issue among college students is routinely a major public health concern, and coronavirus disease 2019 (COVID-19) pandemic may have exacerbated the students' mental health issues which include psychological distress, panic disorder, insomnia, and posttraumatic stress symptoms. However, few studies reached a consensus on the impact of COVID-19 fear on mental health among college students. Therefore, we aimed to conduct a systematic review and meta-analysis that quantitatively synthesized the fear among college students during the COVID-19 pandemic.MethodsPubMed, EMBASE, CINAHL, and PsycINFO electronic databases were systematically searched to identify cross-sectional study reporting the state of COVID-19 fear examined by the Fear of COVID-19 Scale (FCV-19S) published up until November 20, 2021. Methodological quality was complied with the evaluation criteria of the Agency for Healthcare Research and Quality. The random effects model was employed to estimate the pooled mean of FCV-19S score. Subgroup analysis and meta-regression analysis were also conducted. Publication bias was assessed by Begg's test and funnel plot.ResultsA total of 16 studies with a sample size of 11,872 were included. A pooled mean of FCV-19S score was 17.60 [95% confidence interval (CI): 16.41-18.78]. The mean of COVID-19 fear in women (17.11, 95% CI: 16.59-17.64) was higher than that in men (15.21, 95% CI: 14.33-16.08). The highest and lowest pooled means of FCV-19S score were observed in the studies conducted in multiple countries that include Israel, Russian, and Belarus (21.55, 95% CI: 20.77-22.33) and in Europe (16.52, 95% CI: 15.26-17.77), respectively. No significant publication bias was detected by Begg's test.ConclusionsCollege students experienced a moderate level of fear caused by COVID-19 pandemic. It is necessary to design and implement prevention programs that target the mental health of college students.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021287017, identifier: CRD42021287017.